"It was Hard to Prepare without Knowing What I was Preparing for": Latine Youth Experiences of a First-Generation College-Going Group. Issue 1 (31st January 2023) - Havlik, Stacey; Malott, Krista; Wheatcroft, Jaime; Salas, Sylvia
This article describes the experience of participants and facilitators engaging in a psychoeducational group counseling intervention designed to enhance college readiness among Latine first-generation college-going students—those for whom neither parent completed college (National Center for Education Statistics, 2017). The group was designed to increase students' understanding of how their various identities impacted their college preparatory experience and willingness to seek help. Findings suggest that participants recognized the importance of their identities and the way they influenced their help-seeking behaviors. Participants identified similarities among their experiences related to college going while also valuing learning from each other's differences. Last, participants felt a sense of uncertainty and angst about going to college. We also share facilitator experiences.